Analysis of Bored Pile Single Foundation on Light Rail Transit (LRT) Project in Zone 4 of Musi River, Palembang City - Arfan, Muhammad; Setiawati, Mira (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2017)
An experimental study of the baring capacity of a single bored pile foundation to determine the efficiency of the bearing capacity, the method was carried out based on the N-SPT data using the Meyerhof method and the Vesic method (in allpile software). The location of the study was carried out at points P5 and P6 on the LRT Bridge (Light Rail Transit) using a variety of diameters of Ø160, Ø170, Ø180 with depth conditions of 30, 31, 32, 33 meters, and variations of Ø130, Ø140, Ø145 at a depth of 33, 34, 35 , 36 meters with fixed concrete quality, namely the K-350. The results obtained from the single bored pile foundation carrying capacity, at Mayerhof P5 amounted to 15,403,892 kN and using allpile of 16,486.52 kN with a difference of 7%. Whereas in Mayerhof P6 it was 15,554,686 kN and using allpile was 16,022.71 kN with a difference of 3%. The carrying capacity of the largest foundation lies in P5 with a carrying capacity of 16,486.52 kN, while the carrying capacity of the smallest foundation is in P6 with a carrying capacity of 16,022.71 kN. The results of the calculation of the variation in the efficient P5 are Ø130 depth 38.5 m volume 51.123 m3, Ø140 depth 35.5 m volume 54.67 m3 and Ø145 depth 34.5 m volume 56.993 m3 with a carrying capacity of 16,486.52 kN. While in P6 the efficient is Ø130 36.5 m depth volume 48.467 m3, Ø140 35 m depth volume 53.9 m3 and Ø145 depth 34 m volume 56.167 m3 with a carrying capacity of 16.002.71 kN.